Physical, Chemical, and Antioxidant Characterization of Nano-Pomegranate Peel and Its Impact on Lipid Oxidation of Refrigerated Meat Ball. (13th September 2022) - ElBeltagy, Alaa E.; Elsayed, Mahmoud; Khalil, Sabry; Kishk, Yasser F. M.; Abdel Fattah, Abdel Fattah A.; Alharthi, Salman S.
Abstract : Pomegranate peel (CPP), enriched with bioactive constituents, had potent antioxidant features. Therefore, it is worth finding out functional and antioxidant features of the nanoscale pomegranate peel. The nanoscale of pomegranate peel was prepared by ultrafine grinding in a ball mill for 45 min (NPP45) and 90 min (NPP90). The physical (SEM, TEM, FTIR, and XRD) and chemical characteristics (phenolics, flavonoids, DPPH scavenging activity, FRAP, and reducing power) of nanoparticles were studied. The quality aspects of cold stored (5 ± 2°C) meatballs formulated with 0.5% (W/W) of nano-peel powder were evaluated. Similarly, FTIR spectra and XRD patterns were recorded for nano and crude pomegranate peel samples. Generally, grinding the crude peel for 45 and 90 min enhanced its scavenging activity, reducing power, FRAP, total phenolic, and flavonoid by a range of 12.58 to 20.37 and 20.57% to 35.18%, respectively. The addition of crude/nanosized peel to the meat ball diminish (p < 0.05 ) formation of thiobarbituric acid (TBARS), peroxide (PV), and volatile nitrogen and kept the sensory attributes up to 9 days of cold storage. No significant differences were noticed in PV and TBARS of meatballs formulated with 0.5% NPP90 and 0.1% BHT, which suggests the potential use of nanoscale pomegranate peel as natural substitutes to BHT in meat products.